Optimización del sistema de caracterización de parámetros climáticos en mini jardines clónales forestales bajo ambiente protegido. - Román-Muñoz, Frank (Instituto Tecnológico de Costa Rica, 2012)
This document describes the process of research and optimization of the system for characterization of weather parameters in mini clonal forest gardens under controlled environment conditions implemented at a GENFORES2 green house located in Santa Clara, in the Costa Rica Institute of Technology. With the implementation of the project, it will be able to send the recollected information from the sensors through the nodes and upload it to internet. The procedures for the implementation of the project were based on a first assessment of the case done in the location to diagnose the main deficiencies of the employed system one year ago. The results identified the need to implement changes to find a different way to transport the information from the base node to the user access point. For this reason, the architecture of the network was redesigned using a Beaglebone to control a USB modem, which allows the internet access through third generation technology. The I2C communications protocol was used to transmit information between the base node and the Beaglebone. Also, it was necessary to add an additional module of lighting, which allows the extending of the plants’ photoperiod as part of the GENFORES experiments. The optimizations implemented in the software routines allowed to reach the requirements in the decrease of current consume to avoid overheating on the base node. All the reached objectives are important because their contribution with the GENFORES team labor to ensure the improvement and development of forest genetic resources
Proyecto de Graduación ( Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: Red de sensores; Beaglebone; Módem USB; Protocolo I2C; Multimedia Board; Encapsulado de sensores